PENGARUH PEMBERIAN JANTUNG PISANG TERHADAP KECUKUPAN ASI PADA BAYI 0-6 BULAN DITINJAU DARI PENINGKATAN BERAT BADAN DAN PANJANG BADAN BAYI: The Effect Of Banana Heart On Adequacy Of Breast Milk In Infants 0-6 Months In View Of The Increase In Baby's Body Weight And Length - Fitrah Ramadani (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2023)
Breast milk (ASI) is a natural food that can be used, provides a complete source of nutrition for babies, protects mothers and children from disease, and has anti-inflammatory properties. One of the first steps towards a healthy and prosperous life is breastfeeding and to increase breast milk production, pregnant women can consume banana blossoms which are a type of plant that contains lactagogum which has the potential to stimulate the hormones oxytocin and prolactin such as alkaloids, polyphenols, steroids, flavonoids and other substances effectively. in increasing and facilitating milk production. Research purposes The purpose of this study was to analyze the effectiveness of banana buds on the adequacy of breast milk in infants less than 6 months in terms of weight gain. The research method is a quasi-experimental research using a two group pre and post test design, with a total sample of 20 samples divided into 2 groups, namely the control group and the experimental group. The results showed that the average increase in baby weight in the experimental group before being given banana heart vegetables, the mean was 5.090 and after being given the banana flower, it increased to a mean of 5.590 with a mean difference of 0.50 while the mean increase in infant weight in the control group was 4.98 increased to 5.130 with a difference of 0.15. From the results of the independent T test, it can be seen that the p value of 0.02 < 0.05 means that there is a significant difference in the average weight gain of infants in the treatment group given banana heart with the control group not given treatment.